Mulch film: An overlooked diffuse source of organic ultraviolet absorbers in agricultural soil. (1st February 2023) - Li, Bingru; Liu, Qi; Yao, Zhenzhen; Ma, Zhihong; Li, Cheng
Abstract: Ultraviolet absorbers (UVAs) are emerging pollutants of concern owing to their environmental persistence and endocrine-disrupting effects. UVAs are added to agricultural films to prevent UV-induced degradation, potentially leading to the release of UVAs into the soil. In this study, the occurrence of four frequently used UVAs (UV-324, UV-326, UV-328, and UV-531) in film-mulched agricultural soils (using conventional polyethylene films and biodegradable films) was investigated. Results showed that the UVA concentrations were several orders of magnitude higher in film-mulched soil (mean 91.4 μg/kg) than in unmulched soil (mean 0.08 μg/kg), indicating that mulch films are important sources of UVAs released into agricultural soil. Notably, the mean UVA concentration was up to 10 times higher in biodegradable-film-mulched soils than in polyethylene (PE) film-mulched soils; this result is consistent with our finding that the mean UVA concentration was 448 times higher in commercial biodegradable films than in PE films. In simulated migration experiments, UVAs migrated more readily into the soil from the biodegradable film than from the PE film. To our knowledge, this is the first report demonstrating that the use of mulch films may cause the accumulation of UVAs in agricultural soils as non-point sources. In particular, biodegradable plastic mulches can release more UVAs into soils. Graphical abstract: Image 1 Highlights: UV absorber levels were much higher in film-mulched soils than in unmulched soils. Mulch films are important sources of UV absorbers in agricultural soil. Biodegradable mulch films contained more UV absorbers than polyethylene films. UV absorbers are readily leached into soils from biodegradable mulch films.